Celestial Worship and Ecstatic-Visionary Experience - de Souza Nogueira, Paulo Augusto (Journal for the study of the New Testament, 2002)
John’s visions in Revelation not only contain scenes of heavenly worship, but also take place in the context of community worship. In this experience, the community understands itself to be caught up into the angelic worship in heaven. Parallel texts, such as The Ladder of Jacob, The Apocalypse of Abraham, The Ascension of Isaiah, a number of Dead Sea Scrolls and some synagogal prayers, illustrate various dimensions of this phenomenon. In this ecstatic experience the visionary is both representative of, and mediator for, his community, gaining access to heavenly power in ways not dissimilar to magical liturgies. Thus the early Christian and Jewish accounts of heavenly journeys and worship are not just literary phenomena: they express a powerful and popular ecstatic religiosity.